Analysis of Electronic Load Controller with Bidirectional Converter in Self-Excited Induction Generator - Andi Pawowoi; Wahyu Rizki Muslyadi; Refdinal Nazir; Fajril Akbar (Jurusan Teknik Elektro Universitas Andalas, 2022)
Induction generators are widely used in small-scale power plants driven by renewable energy, such as wind, mini/micro-hydro, tidal wave, biomass, biogas, etc. In applying this generator to a micro-hydropower plant, it is usually equipped with an ELC (Electronic Load Controller), which regulates the frequency to remain constant at a safe tolerance limit (49.8 – 50.2 Hz). However, this system is still not optimal because the ELC dumps its excess power into the dummy load. This paper proposes an ELC system that can adjust the frequency to remain constant without wasting excess power from the generator. This system uses the working principle of a bidirectional converter, which can regulate the flow of power from the generator and dummy load in two directions. In the proposed system, the dummy load uses a battery to store excess electrical energy and be utilized and reused when needed. Performance analysis of the proposed system uses simulation with MATLAB Simulink software. The induction generator used has a voltage specification of 380 Y, 50 Hz, 1420 rpm, 3.5 A, and 1.5 kW. The analysis results show that the developed ELC design can adjust the frequency in the value range of 49.98-50.01 Hz during load changes with a range of 955 Watt to 1.045 Watt, with the response time reaching its steady-state value of 0.1-0.4 seconds.